Broadband and economic growth: a reassessment. Issue 1 (2nd January 2020) - Mayer, Walter; Madden, Gary; Wu, Chen
ABSTRACT: The principal question addressed by this study is: is broadband network penetration a robust determinant of economic growth? We employ a dynamic panel data threshold model with fixed effects to allow for variation in the parameters by income groups to investigate the impact of broadband speed and its interaction with penetration on growth. We find that penetration is statistically insignificant with speed (positively) and its interaction with penetration (negatively) significantly impacting on growth. An additional insight is that for a generic shock experienced by LIC, on average, 40% of the total impact is accomplished immediately, with about 80% occurring within four quarters. The results are intended to inform governments that increased speed is more important for countries with lower penetation, the returns expected from these ambitious targets are neither immediate nor universally assured; and critically the magnitude of the benefit relies on the initial level of national economic development.